Trends and distribution of Chinese cassava production and use, 1820-1984 (A technological and economic examination of historical development and future potential) - Stone, B (International Center for Tropical Agriculture, 1987)
Cassava was probably introduced into China from South America around 1820. The main production area is in the southern province of Guandong and the Guangxi Zhuang Autonomous Region. With the catastrophic famines in the 60s, efforts to spread cassava cultivation northward intensified considerably. Due to lack of reliable national data, production series for these 2 regions are synthesized for the period 1950-84. Data are also provided on yields, production systems, production costs, and labor utilization. The country has a long history of research and development, the 1st book on cassava planting methods being published in 1900. There are a no. of institutes involved in research and development; the 2 most important are the South China Tropical Crops Research Academy, which has concentrated on selecting and disseminating improved var., and the Zhejiang Province Subtropical Crops Institute in Pingyang, which has introduced var. in the north. Current utilization may run 60-65 percent for feed, 15-20 percent for starch, 2-4 percent for tapioca production, and 10-20 percent for direct human consumption. Markets and demand are analyzed. (CIAT)